Management of Arteriovenous Fistula After Successful Kidney Transplantation in Long-Term Follow-Up - Janeckova, Jana; Bachleda, Petr; Utikal, Petr; Orsag, Jirir (Transplant international, 2024)
Arteriovenous fistula (AVF) is the best method of vascular access for hemodialysis. This approach can lead to several complications, such as hyperkinetic heart failure due to a hyperfunctional AVF or dilatation of the feeding artery. These are late complications, especially in patients after a successful kidney transplantation. An observational study was performed focusing on patients more than 12 months after kidney transplantation. The AVF was evaluated by ultrasound and, if the outflow exceeded 1.5 L/min, an echocardiogram was performed. Surgical management was indicated if the cardiac index was higher than 3.9 L/min/m2 or upon finding a brachial artery aneurysm. A total of 208 post- kidney transplantation patients were examined over a 3-year period, of which 46 subjects (22.11%) had hyperfunctional AVF and 34 cases (16.34%) of feeding artery dilatation were determined. In total, 40 AVF flow reduction and 6 AVF ligation procedures were performed. The median AVF flow before and after the reduction was 2955 mL/min and 1060 mL/min, respectively. Primary patency after flow reduction was 88.3% at 12 months. Late AVF complications in patients following kidney transplantation are quite common. It is necessary to create a screening program to monitor AVFs in these patients.
Keywords: AVF ligation; Humans; průchodnost cév; lidé středního věku; echokardiografie; Arteriovenous Shunt, Surgical; Echocardiography; Renal Dialysis; Female; Aged; dospělí; screening; dialýza ledvin; senioři; lidé; arteria brachialis; AVF flow reduction; Adult; Postoperative Complications; Brachial Artery; transplantace ledvin; pooperační komplikace; ženské pohlaví; Follow-Up Studies; hyperfunctional AVF; Male; Middle Aged; arteriovenózní zkrat; Vascular Patency; Kidney Transplantation; mužské pohlaví; následné studie; kideny transplantation